Effect of Er,Cr:YSGG and Er:YAG laser irradiation on the adhesion of blood components on the root surface and on root morphology - de Oliveira, Guilherme José Pimentel Lopes [UNESP]; Theodoro, Letícia Helena; Junior, Elcio Marcantonio [UNESP]; Sampaio, José Eduardo Cezar [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP] (FapUNIFESP (SciELO), 2012)
The aim of this study was to conduct an in vitro evaluation, by scanning electron microscopy (SEM), of the adhesion of blood components on root surfaces irradiated with Er,Cr:YSGG (2.78 μm) or Er:YAG (2.94 μm) laser, and of the irradiation effects on root surface morphology. Sixty samples of human teeth were previously scaled with manual instruments and divided into three groups of 20 samples each: G1 (control group) - no treatment; G2 - Er,Cr:YSGG laser irradiation; G3 - Er:YAG laser irradiation. After performing these treatments, blood tissue was applied to 10 samples of each group, whereas 10 samples received no blood tissue application. After performing the laboratory treatments, the samples were observed under SEM, and the resulting photomicrographs were classified according to a blood component adhesion scoring system and root morphology. The results were analyzed statistically (Kruskall-Wallis and Mann Whitney tests, α = 5%). The root surfaces irradiated with Er:YAG and Er,Cr:YSGG lasers presented greater roughness than those in the control group. Regarding blood component adhesion, the results showed a lower degree of adhesion in G2 than in G1 and G3 (G1 × G2: p = 0.002; G3 × G2: p = 0.017). The Er:YAG and Er,Cr:YSGG laser treatments caused more extensive root surface changes. The Er:YAG laser treatment promoted a greater degree of blood component adhesion to root surfaces, compared to the Er,Cr:YSGG treatment.
Keywords: Blood; Lasers; Microscopy, Electron, Scanning; Root planing